Investigating early changes in cognitive ability in the cognitively healthy and early‐stage cognitively impaired older adult populations: Neuropsychology/Early detection of cognitive decline with neuropsychological tests. (7th December 2020) - Idowu, Mojitola; Parton, Andrew; Szameitat, Andre
Abstract: Background: Decline in cognitive ability is well understood to occur due to advanced age and pathological impairment. However, not all affected aspects of cognitive ability deteriorate at the same rate (Petersen, RC, et al., 1997; Craik, FI, and Salthouse TA, 2000, 2008, 2011; Salthouse, TA, 2009, 2012). In this study, we research how executive function abilities (mental processes that regulate and control our cognition) differ between cognitively healthy older adults and individuals living with Mild Cognitive Impairment (MCI) and early‐stage Alzheimer's disease (AD). Assessment was focused on four areas of executive functions dual‐tasking, inhibition, shifting and updating commonly utilised in everyday life (Miyake, A, et al ., 2000; Alvarez, JA, and Emory, E, 2006; Suchy, Y, 2009; Baddeley, A., 2012). The aim is to better understand the nature and rate of deterioration as a means to aid in early detection and intervention for both conditions. Method: We aim to assess approximately 30 cognitively healthy older adults, and a combination of 30 individuals living with MCI and early‐stage AD on four different aspects of executive functions, i.e. dual‐tasking, inhibition, shifting and updating. Two separate tasks will be utilised to measure each EF, dual‐tasking (the Test of Everyday Attention dual‐task telephone search subtest and Psychological Refractory Period paradigm task), inhibition (the Hayling Sentence Completion test and Stroop task), shifting (the Trail Making Test and a task switching test), and updating (the backward digit recall span test and a N‐back task). Result: Data collection is ongoing. Conclusion: We predict better cognitive ability will be evident in the healthy older adult group, followed by the MCI and then the early‐stage AD groups. However, we expect dual‐tasking and updating ability to be most severely affected in individuals living with early‐stage AD and then shifting with inhibition showing most preservation.